2007
DOI: 10.1007/s11430-007-5015-4
|View full text |Cite
|
Sign up to set email alerts
|

A study on an oligotrophic bacteria and its ecological characteristics in an arid desert area

Abstract: An oligotrophic bacterium was isolated from the biological soil crust underlayer in the Xinjiang Gurbantunggut Desert. It was numbered SGB-5, G + . Cell size is (0.328-0.746) µm×(0.171-0.240) µm. Raised colony is white, roundness and its diameter is 5 mm. The strain is a facultative aerobe. It was able to grow in conditions of 1-15 mg·C·L −1 culture medium at 10-50℃. The strain's optimum growth temperature is 37℃. The range of its optimum growth pH is 8-9. A large amount of extracellular mucopolysaccharide was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…An unidentified bacterium isolated from biological soil crusts (BSCs) from the Gurbantünggüt Desert stabilized sand surface, producing aggregation and slowing the soil water evaporation after only 8 days of inoculation. In addition, the EPS of the bacterium produced the conglutination of sand particles, as observed by scanning electron microscopy ( HuiXia et al, 2007 ). Another isolate from Gurbantünggüt Desert, Paenibacillus KLBB0001 – a strong EPS producer – was inoculated in the desertic soil to improve the recovery of BSCs.…”
Section: Application Of Eps On Soil Aggregationmentioning
confidence: 99%
“…An unidentified bacterium isolated from biological soil crusts (BSCs) from the Gurbantünggüt Desert stabilized sand surface, producing aggregation and slowing the soil water evaporation after only 8 days of inoculation. In addition, the EPS of the bacterium produced the conglutination of sand particles, as observed by scanning electron microscopy ( HuiXia et al, 2007 ). Another isolate from Gurbantünggüt Desert, Paenibacillus KLBB0001 – a strong EPS producer – was inoculated in the desertic soil to improve the recovery of BSCs.…”
Section: Application Of Eps On Soil Aggregationmentioning
confidence: 99%
“…The characteristics of identified bacteria and cyanobacteria have been summarized in Supplementary Tables 1 and 2. Based on desired characteristics explained before, the Azotobacter and Bacillus subtilis strain from bacteria and also Nostoc, Oscillatoria and Lyngbya from cyanobacteria were selected as the most appropriate microorganisms to be applied for targeting the study goals. In this regard, Huixia et al (2007) introduced Oligotrophic bacteria including Bacillus as suitable bacteria for soil characteristics improvement in deserts. Maqubela et al (2009) reported that the soil aggregate and carbon sequestration increased after Nostoc inoculation on corn field soil.…”
mentioning
confidence: 99%
“…The response of oligotrophic bacteria different from other groups of microorganisms may result from different abilities of microorganisms to degrade plant protection products and from oligotrophic bacteria being microorganisms with low nutritional requirements. In addition, they have a membrane which constitutes a barrier against harmful environmental factors (HuiXia et al 2007). An increase in the count of oligotrophic bacteria in soil supplemented with pethoxamid and terbuthylazine (the active substances of the herbicide Successor T 550 SE) was also observed in the previous studies by our team, conducted under strictly controlled conditions (Tomkiel et al 2014).…”
Section: Resultsmentioning
confidence: 99%